Chalcone derivatives: synthesis, in vitro and in vivo evaluation of their anti-anxiety, anti-depression and analgesic effects - Higgs, Josefina (2019)
Anxiety disorders, depression and pain are highly prevalent pathologies. Their pharmacotherapy is associated with unwanted side effects; hence there is a clinical need to develop more effective drugs with fewer adverse reactions. Chalcones are one of the major classes of naturally occurring compounds. Chalcones and their derivatives have a huge importance in medicinal chemistry, displaying a wide range of pharmacological activities including anti-inflammatory, antimicrobial, antioxidant, cytotoxic and antitumor actions. The aim of this work was to evaluate chalcone effects on different targets involved in these pathologies. We have synthesized a series of simple chalcone derivatives taking common structural requirements described in literature related to their anxiolytic-like, antidepressant-like and/or antinociceptive properties into account. Furthermore, their potential in vitro effects towards different targets involved in these pathologies were evaluated. We have obtained twenty chalcones with moderate to high yields and assessed their ability to bind distinctive receptors, from rat brain homogenates, by displacement of labelled specific ligands: [ 3 H] FNZ (binding site of benzodiazepines/GABA A ), [ 3 H] 8-OH-DPAT (serotonin 5-HT 1A ) and [ 3 H] DAMGO (μ-opioid). Those compounds that showed the better in vitro activities were evaluated in mice using different behavioural tasks. In vivo results showed that 5′-methyl-2′-hydroxychalcone (9) exerted anxiolytic-like effects in mice in the plus maze test. While chalcone nuclei (1) revealed antidepressant-like activities in the tail suspension test. In addition, the novel 5′-methyl-2′-hydroxy-3′-nitrochalcone (12) exhibited antinociceptive activity in acute chemical and thermal nociception tests (writhing and hot plate tests). In conclusion, chalcones are thus promising compounds for the development of novel drugs with central nervous system (CNS) actions.